Brands Gamified: concept, applications and challenges - Malhotra , Suzanee (Gyan Management Journal, 2021)
Purpose: This article aims to contribute to build an understanding of the new concept of  gamification that has made a buzz for itself recently. Despite being a trendy research topic, it  still lacks sufficient literature studies to understand this concept from all angles. . This article  initially aims to provide an introduction to this trendy concept along with its applications and  examples.Proposed Design/Methodology/Approach: Inspired from Dr. Edward de Bono’s, six thinking  hats this article provides a new and detailed analysis of the gamification concept from different  angles. 12 Qualitative interviews were put to thematic data analysis under Nvivo software for  coming to the research findings that are very interesting and one of its kind. Findings: The findings of this study are very crucial for brands involved and interested in the  business of gamification. From the positive and creative sides that this concept offers, this  paper has also indicated the negatives, facts and figures, feelings aspect as well as the planning  required for this concept. Practical/Theoretical implications: With many new trends emerging in the world of digital  marketing over the past couple of years, gamification has created a buzz for itself. An  innovative yet appealing tool to attract consumers towards brands and keep them emotionally  involved, it has been increasingly used across different types of brands. Originality/value: A novel approach for understanding the brand gamification concept on  6thinking hats approach is presented in the study. This article provides a base for future studies  from an empirical angle in this domain that has not been taken up in this particular study. Limitations: This paper used qualitative study and the quantitative study has not been addressed  in this article.
Keywords: Artificial intelligence; Gamification; Mobile Culture; Six Thinking Hats; Thematic analysis; Virtual Recreation